Modeling the effect of heat treatment on fatty acid composition in home-made olive oil preparations - Dordevic, Dani; Kushkevych, Ivan; Jancikova, Simona; Zeljkovic, Sanja Cavar; Zdarsky, Michal; Hodulova, Lucia (Open life sciences, 2020)
The aim of this study was to simulate olive oil use and to monitor changes in the profile of fatty acids in home-made preparations using olive oil, which involve repeated heat treatment cycles. The material used in the experiment consisted of extra virgin and refined olive oil samples. Fatty acid profiles of olive oil samples were monitored after each heating cycle (10 min). The outcomes showed that cycles of heat treatment cause significant (p < 0.05) differences in the fatty acid profile of olive oil. A similar trend of differences (p < 0.05) was found between fatty acid profiles in extra virgin and refined olive oils. As expected, the main differences occurred in monounsaturated fatty acids (MUFAs) and polyunsaturated fatty acids (PUFAs). Cross-correlation analysis also showed differences between the fatty acid profiles. The most prolific changes were observed between the control samples and the heated (at 180°C) samples of refined olive oil in PUFAs, though a heating temperature of 220°C resulted in similar decrease in MUFAs and PUFAs, in both extra virgin and refined olive oil samples. The study showed differences in fatty acid profiles that can occur during the culinary heating of olive oil. Furthermore, the study indicated that culinary heating of extra virgin olive oil produced results similar to those of the refined olive oil heating at a lower temperature below 180°C.
Keywords: polyunsaturated fatty acids; virgin olive oil; refined olive oil; cross-correlation analysis; monounsaturated fatty acids; saturated fatty acids